The effect of a moveable collateral registry on MSME access to finance: Evidence from Malawi - Susan Pendame; Joseph Oscar Akotey (Cogent Economics & Finance, 2023)
This study explores to answer the question: does the introduction of a moveable collateral registry lead to significant increase in access to credit to micro, small and medium-sized enterprises? We examine this question through a unique dataset collected from the moveable collateral registry and commercial banks in Malawi. The findings indicate that the introduction of the registry in Malawi has led to marginal increase in MSME's access to bank credit. Real property, however, remains the preferred collateral and ability to repay the loan is the most important consideration amongst banks in assessing whether to lend to micro, small and medium-sized enterprises. We recommend the registry to integrate into its programs financial literacy training for MSMEs, and credit guarantee schemes to mitigate the perceived high risk associated with small enterprises. This will equip the MSMEs to keep proper accounts and enhance their access to the registry and bank credit.
Keywords: 330; access to credit; Malawi; moveable assets; moveable collateral registry; MSMEs